KINERJA PEGAWAI PADA BAGIAN ADMINISTRASI DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN GORONTALO - Umar Sako Baderan; Robin Pakudu; Darwin Ismail (LPPM Universitas Muhammadiyah Gorontalo, 2022)
This research aims to find out how far the performance of Administrative Section Employees at the Secretariat of the Regional People's Representative Council of Gorontalo Regency. The research method used is a qualitative approach with a descriptive research type. The results found that the performance of employees in the administrative section of the secretariat office had been going quite well. It can be seen there are 5 (five) indicators related to employee performance in which 3 (three) indicators are in accordance with the analysis found problems related to the employee's performance. The indicators of Quantity, Quality and Attendance are problematic indicators that reinforce the problems found at the time of observation namely 1) Low innovation and creativity of employees in carrying out work; 2) Manual mail administration system; and 3) Lack of discipline in the work of employees and not in accordance with the job desk. Furthermore, other indicators, namely reliability and ability to work together, have been good and as expected. Employees can be relied on at work and can work well together in completing the work ordered by their superiors